A STUDY OF THE FACTORS THAT INFLUENCE RE-VISIT DECISION OF YOUNG CUSTOMERS TO QSR OUTLETS IN PUNE - Botre, Pralhad; Wadajkar, Vishal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The QSR restaurants are getting popular amongst the young customers due to varied reasons like quick mouthwatering tasty food items, very casual kind of environment, friendly service etc. These are the primary requisites of the young customers. The favourable conditions like high disposable income, busy lifestyle and both spouse work culture have accelerated the progressive development of QSR in Pune region. The QSR market is growing significantly from year by year. Due to this every year number of new QSR are also increasing leading to a highly competitive market. Thus, to survive in this competitive market, it is essential that each QSR owners should examine their customers. They should identify the factors that inspire the customers to visit or re-visit a QSR in a rank of priorities and concentrate to excel so that they can have a winning edge over the competitors. This research revolves around the customers who are the main stake holders and reason for the existence of QSR. It focuses on the factors that are responsible for the customers satisfaction from Pune region like food quality, food variety, food service, pricing, ambience, décor, location etc. The data collected was analysed using descriptive analysis and Paired Sample t-test. The resultant led to comprehend the factors that are the priority of the QSR customers from Pune for evaluating a QSR in accordance with their satisfaction. The Customer Satisfaction is very essential for the easy word of mouth marketing and revisiting of the customers to the QSR. This is of paramount importance to ascertain a progressive and sustainable growth of the QSR industry.